Students as contested: Exploring issues of student identity and identification in educational spaces - Kenway, Ashley; Wilkinson, Phil; Dowden-Smith, Kieron (International Journal for Students as Partners, 2019)
This article explores issues of student identity and identification through a third-space theory lens. In addition, it positions this use of third-space theory as contributory to Students-as-Partners (SaP) approaches to teaching and learning. Naturally, this research was constructed as a SaP project, and research was undertaken as a collaboration between two undergraduate students and their lecturer. The literature review and student interviews presented here were conducted by the student co-researchers and interviews involved their BSc Cyber Security Management peers. These interviews unpacked constructions of student identity, student-lecturer relationships, and professional experiences. Thematic analysis of these interviews is presented reflectively with reference to student and lecturer perspectives. Finally, this article argues that for SaP to be successful it is necessary to critically examine the “student” identifier.